Hippocampal remapping and its entorhinal origin - Latuske, Patrick; Kornienko, Olga; Allen, Kevin (Frontiers in behavioral neuroscience, 2018)
The activity of hippocampal cell ensembles is an accurate predictor of the position of an animal in its surrounding space. One key property of hippocampal cell ensembles is their ability to change in response to alterations in the surrounding environment, a phenomenon called remapping. In this review article, we present evidence for the distinct types of hippocampal remapping. The progressive divergence over time of cell ensembles active in different environments and the transition dynamics between pre-established maps are discussed. Finally, we review recent work demonstrating that hippocampal remapping can be triggered by neurons located in the entorhinal cortex.
Gesehen am 03.04.2018